Penerapan Metode Luther Sutopo dalam Pembuatan Augmented Reality Candi Muara Takus Berbasis Android - Nasari, Fina; Sepdu Dehiya, Yogi; Anggara, Yogi (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2025)
Tourism in Indonesia is experiencing rapid growth thanks to various unique local destinations. In Riau Province, Kampar Regency boasts significant tourism potential, including Candi Muara Takus, a historical Mahayana Buddhist site. Unfortunately, limited promotion has led to the site's lack of widespread recognition. This study aims to develop an Android-based Augmented Reality (AR) application that presents Candi Muara Takus interactively, using the Luther-Sutopo method, which includes the stages of concept, design, material collection, production, Testing, and distribution, with Unity, Vuforia, and Blender employed for asset creation. Testing results indicate that the AR application successfully installed and operated on three Android Devices-Tecno Pova 5, Oppo A18, and Poco M3 Pro 5G with a 100% success rate on each Device. Feasibility Testing using Black Box Testing confirmed that all application features functioned as expected, including navigation and exit functions. Additionally, marker Testing showed that the system could read markers effectively if at least 50% of the marker image was visible, while markers were unreadable at 25% visibility. The AR application aims to enrich the experience of exploring Candi Muara Takus, present information interactively, and support broader tourism promotion. It is also expected to enhance public understanding and appreciation of the site's history, potentially attracting more tourists and supporting local economic growth through the tourism sector.